THE EFFECTS OF PRODUCT QUALITY AND PRICE ON BUYING DECISION FOR COFFEE PRODUCT AT STRADA COFFEE, SEMARANG - Prasetyon Sepsi Winarno (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
This research aims to explore the effects of product quality and price on buying decision for coffee product by Strada Coffee in Semarang. Sample size in this research is 96 respondents, while data are gathered by distributing Likert-scale questionnaire to all coffee consumers of Strada Coffee Semarang. Variables studied in this research are product quality and price as independent variables and buying decision variable as dependent variable. The findings reveal that product quality has effect on buying decision, while price has no effect at all.